Peculiarities of the distribution and expression dynamics of apoptosis marker Bax in patients with rectal cancer under the influence of neoadjuvant chemoradiotherapy with the usage of nitric oxide precursor - V. V. Golotyuk (Patologìâ)
The aim of research – to determine the proapoptotic Bax protein expression peculiarities in the intact intestine and tumor of patients with rectal cancer under the influence of neoadjuvant chemoradiotherapy (NHRT), including the polyradiomodification using Ftorafur and Tivortine.